2013
DOI: 10.1098/rsob.130156
|View full text |Cite
|
Sign up to set email alerts
|

Towards an evolutionary theory of the origin of life based on kinetics and thermodynamics

Abstract: A sudden transition in a system from an inanimate state to the living state—defined on the basis of present day living organisms—would constitute a highly unlikely event hardly predictable from physical laws. From this uncontroversial idea, a self-consistent representation of the origin of life process is built up, which is based on the possibility of a series of intermediate stages. This approach requires a particular kind of stability for these stages—dynamic kinetic stability (DKS)—which is not usually obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
168
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 178 publications
(171 citation statements)
references
References 60 publications
1
168
0
2
Order By: Relevance
“…From aw ider perspective,o ur results suggest that other (pre)biological subsystems based on hydrolytically labile components might have been subject to optimization through energy-dissipative recycling. [18] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From aw ider perspective,o ur results suggest that other (pre)biological subsystems based on hydrolytically labile components might have been subject to optimization through energy-dissipative recycling. [18] …”
mentioning
confidence: 99%
“…However,r ather than just degrading RNA, am ore plausible scenario would embrace recycling, with formation of new 3',5'-bonds through repair of the broken linkages.Atheoretical model addressing this was proposed in 1977 by Usher, [14] who envisioned that day/night alternation on the early earth could have created suitable conditions for the degradation of 2',5'-bonds and subsequent joining of the resulting fragments.H owever,U sher invoked dry-state non-templated oligomerization for the joining chemistry,a nd this is known to only slightly favor the formation of natural linkages [15] and is limited by unfavorable equilibrium considerations to producing short fragments. [16] Furthermore,hydrolysis followed by non-templated synthesis would not allow the propagation of sequence information and, accordingly,w es ought as cheme whereby 2',5'-bonds could be "corrected" to 3',5'-bonds through proofreading with retention of sequence.W er easoned that any such repair process would have an energetic cost, and hence sought an energy-dissipative cycle [17,18] that would combine selective hydrolysis of duplex 2',5'-linkages with templated 3',5'-selective ligation chemistry. [19] We recently reported that templated ligation of mixtures of short oligonucleotides terminating with 2'-a nd 3'-monophosphates can be made 3',5'-selective by means of sequential acetylation and ligation chemistry.T he selectivity derives from preferential 2'-O-acetylation of 3'-monophosphate-terminated oligomers,w hich can then undergo regiospecific ligation.…”
mentioning
confidence: 99%
“…the first protocells may have had a degree of autonomy similar to that of present day free-living microorganisms. The idea that replicative systems exhibit a novel and specific form of stability, namely Dynamic Kinetic Stability, has been developed by Addy Pross (Pross 2011(Pross , 2012Pross and Pascal 2013). Stability is understood in this view as persistence in time.…”
Section: Prebiotic Chemistry New Areamentioning
confidence: 99%
“…In response to these probing questions, directed toward clarifying the nature of the chemistrybiology connection, modern biology has taken a defensive posture and battened down the hatches. The unstated but implicit message in contemporary biology appears to be: yes, there are innumerable apparent contradictions when biology is directly confronted with physics and chemistry [2,[11][12][13][14]. However, since the physical sciences have not provided biology with the appropriate conceptual and methodological tools for resolving these contradictions, biology can avoid these awkward questions by fencing itself off from the physical sciences.…”
Section: Introductionmentioning
confidence: 99%
“…By what process and based on what physicochemical principles was it possible for matter to be transformed from the relatively well-understood inanimate state into that extraordinarily complex and thermodynamically unstable animate state. Certainly from a purely thermodynamic perspective such a transition would seem to be spectacularly improbable [11][12][13].…”
Section: Introductionmentioning
confidence: 99%